How do I find the sum of 6(-2.1k-2) + (7k+5)
1 answer:
Answer:
-5.6k-7
Step-by-step explanation:
you'd start by multiplying 6 by everything in the first pair of parentheses:
6(-2.1k-2)= (-12.6k-12)
then you'd add the like terms together:
(-12.6k-12)+(7k+5)= -5.6k-7
You might be interested in
Answer:
a = logx 1/x^30/6
b = 28
c = -11
Step-by-step explanation:
Answer:
Step-by-step explanation:
It will be b because you will have to time $3.50P140= 490
Answer:
4
Step-by-step explanation:
Root(48)/Root(3)
= root(48/3)
= root(16)
=4